MANAJEMEN DAN TEKNIK KEPALA SEKOLAH DALAM MELAKSANAKAN PROGRAM SUPERVISI DI SEKOLAH - Indri Febrianti; Dimas Dwika Syahramanda; Ardin Rizky Andre Sagala; Salwa Salsabila; Rani Zaskia Ariesky; Inom Nasution (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2023)
The principal has a very important role in determining the quality and success of education in a school. Through supervision program activities, school principals can see how teachers are performing and can be used as evaluation material for further teacher performance improvement. This study uses the method of library research (library research), which is based on reference sources and theories to obtain research data. In obtaining research data, researchers collected and analyzed sources from Google Scholar database articles starting from the 2011-2022 period, related to educational supervision. The general purpose of supervision is to provide technical assistance and guidance to teachers (and other school staff), so that these staff can improve the quality of their work, especially in carrying out tasks, namely the teaching and learning process. This research is expected to be able to teach and add to knowledge about how school principals manage and technique in implementing supervision programs so that all predetermined plans can be carried out effectively and efficiently.